PERTUNJUKAN DIDONG JALU PERSPEKTIF THE DAILY OF TOLSTOY’S AESTHETICS EXPRESSIVISM - Putra Afriadi (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
ABSTRACTThis study aims to analyze the performances of Didong Jalu in an aesthetic context. The research method is qualitative with an interdisciplinary approach. The research location was in Toweren Takengon village, Central Aceh Regency. Data sources namely primary data sources include artists, literature and community leaders, then secondary data sources include books, and references from previous researchers. Data collection techniques consist of observation, interviews, and document studies. The data validity technique uses data triangulation. Data analysis techniques consist of reduction, data presentation, and data verification stage.Keywords: Didong Jalu, Performance ABSTRAKPenelitian ini bertujuan untuk menganalisis pertunjukkan Didong Jalu dalam konteks estetika. Metode penelitian adalah kualitatif dengan pendekatan interdisiplin. Lokasi penelitian di kampung Toweren Takengon Kabupaten Aceh Tengah. Sumber data yakni sumber data primer meliputi seniman, kepustakaan dan tokoh masyarakat, kemudian sumber data sekunder meliputi buku, dan referensi dari peneliti terdahulu. Teknik pengumpulan data terdiri atas observasi, wawancara, dan studi dokumen. Teknik keabsahan data menggunakan triangulasi data. Teknik analisis data terdiri atas reduksi, penyajian data, dan tahap verifikasi data.Kata kunci: Didong Jalu, Pertunjukan in